Trauma and Self-Narrative in Virtual Reality: Toward Recreating a Healthier Mind - Georgieva, Iva (Frontiers in ICT, 2017)
This study discusses the concept of virtual selves created in the virtual spaces (e.g. Social Network Services or Virtual Reality). It analyzes the activities in the different virtual spaces and claims that experience gained there can be transferred to real life. In respect to that, the effects of the Virtual Reality treatment on the self, as well as the concept of creating a life story are analyzed as interconnected. The research question which arises from these considerations is how to look at psychological trauma in order to explain the effectiveness of the usage of Virtual Reality for treatment of traumatic disorders. The proposal in the study is to see trauma as a shift in the normal storyline of the narrative people create. With this concept in mind, it might be possible to support the claim that reliving traumatic events, regaining control over one’s life narrative and creating new stories in the Virtual Reality aids the treatment process in the search for meaning and resolution in life events. Considering the findings of researchers who argue in the field of self-narrative and traumatic treatment, as well as researchers on virtual selves, virtual spaces and Virtual Reality, this study discusses the virtual as a possible medium to experience narratives and utilize those narratives as better explanatory stories to facilitate the therapeutic process of recovery and self-recreation. This study supports the idea that Virtual Reality can be used to visualize patients’ narratives and help them perceive themselves as active authors of their life’s story by retelling traumatic episodes with additional explanation. This experience in the Virtual Reality is utilized to form healthier narratives and coping techniques for robust therapeutic results that are transferred to real life.